Seeing through the eyes of the teacher? Investigating primary school teachers' professional noticing through a video-based research methodology. Issue 5 (20th October 2019) - Xu, Lihua; Widjaja, Wanty; Ferguson, Joseph
ABSTRACT: Digital video technology has been increasingly employed to investigate teacher professional noticing. While extensive research has been undertaken to explore the specialised knowledge base underlying teacher professional noticing, there is a need to more closely examine the methodological consequences of video-based approaches for understanding the nature of professional noticing. This paper draws upon a recent study that investigated primary school teachers' professional noticing of mathematics and science classrooms to discuss issues, challenges, and opportunities that emerge with a video-based research approach. In this study, the latest video technology was employed to allow primary school teachers to take active roles in capturing, selecting and reflecting on significant classroom events on their own and with colleagues. Drawing upon examples from this study, this paper highlights the methodological potential and challenges of video-based approaches to investigating teacher noticing in classrooms, and discusses how this noticing relates to reflection stimulated by classroom videos. It further reveals the tension between the dual priorities of empowering the teacher participants in research and enabling valid interpretations by the researchers in an attempt to gain insight into the complexity of teachers' professional noticing.